Elementos que influyen en el desarrollo de la actividad ganadera tropical en el Ecuador. - Garzón Alcívar, José Alejandro (2022)
The objective of this document is to examine the elements that influence the development of tropical livestock activity in Ecuador, in the same way that livestock in the tropics are in danger due to high temperatures, relatively humid. These must be added to other very important external and internal elements specific to the area, such as food, infectious and parasitic diseases. These conditions affect not only milk production, but also the normal growth and fertility of these animals, although livestock tends to develop worldwide, however, the production areas can be divided into extensive and complementary areas, and in intensive and main areas for self-consumption, in which there are several factors that affect the growth of animals, such as the softness of the soil, access to water, adequate climate in terms of humidity, temperature, vegetation and fodder for food , therefore indicates that the influencing elements are temperature, climate, environment, water, feeding, which affect cattle in the tropics and have an important role, not only in the food that the animal eats, but also that these elements are involved in the development of the animal, which, being at high temperatures, suffers from stress and does not allow them to obtain a good performance and despite that, to have a better the quality of the product, as well as the implementation of new alternatives allows us to obtain a healthy and nutritious food source that our livestock requires, the conservation of forage is an alternative that is used in livestock farms to obtain in times of abundance and be able to transform it into a product to be used in difficult times.